ПРОБЛЕМА ЗАБЕЗПЕЧЕННЯ ПРИНЦИПУ ЕКОЛОГІЧНОЇ СПРАВЕДЛИВОСТІ ЯК ФУНДАМЕНТАЛЬНОЇ ЗАСАДИ СТАЛОГО РОЗВИТКУ - Hudima, T.S. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2018)
The article considers the problem of ensuring the principle of ecological justice as the fundamental basis of sustainable development, in particular the unequal distribution of environmental risks and the realization of the people’s right to a clean and safe environment. The principle of social justice must be supplemented with ecological content (both at the level of domestic legislation and in practice). In particular, the reduction of social injustice must be a condition for ensuring environmental justice.To this end, mechanisms should be used to lobby ecological rights and interests of the population and public associations of nature protection agents; advisory assistance from state authorities; educational and informational support by scientific institutions, information centers, higher education institutions, etc. Taking into account that the resolution of issues related to the reduction of environmental risks, the location and construction of environmentally hazardous facilities, the guarantee of a safe environment, etc. relate to the competence of various state bodies, a closer interagency cooperation between the Ministry of Regional Development, Building and Housing and Communal Services; Ministry of Industrial Policy; Ministry of Health; Ministry of Energy and Coal Industry, etc. Monitoring of compliance of national environmental legislation with international standards and regulations is of great importance in this direction; implementation of environmental legislation (in particular by developing and implementing a mechanism for joint monitoring groups from among representatives of central and local government bodies, experts, the public to monitor compliance with environmental legislation), as well as to increase accountability of central and local authorities. REFERENCES